Engineering Asset Management c - Mathew, Joseph; Kennedy, Jim.; Ma, Lin.; Tan, Andy.; Anderson, Deryk; SpringerLink (Online service) (London : Springer London, 2006)
This text represents state-of-the-art trends and developments in the emerging field of engineering asset management as presented at the First World Congress on Engineering Asset Management (WCEAM) held in Australia in July 2006. The First WCEAM brings together four major international conferences: The Asia Pacific Conference on Systems Integrity and Maintenance (ACSIM) hosted by CRC for Integrated Engineering Asset Management (CIEAM) The Condition Monitoring Conference hosted by the British Institute of Non-Destructive Testing, (BINDT) The Intelligent Maintenance Systems Conference (IMS) hosted by the IMS Center in the USA, and The International Conference of Maintenance Societies (ICOMS®2006) hosted by the Maintenance Engineering Society of Australia (MESA). The Proceedings of the First World Congress on Engineering Asset Management (WCEAM) 2006 is an excellent reference for practitioners, researchers and students in the multidisciplinary field of asset management, covering topics such as: Strategic asset management Risk management in asset management Asset data warehousing, data mining and fusion Asset condition monitoring and intelligent maintenance Intelligent sensors and devices Fault diagnosis and prognostics Deterioration and preservation models for assets Human dimensions in integrated asset management Design and life-cycle integrity of physical assets Maintenance strategies in asset management Asset performance and level-of-service models Information systems and knowledge management Optimisation decisions in asset management Financial analysis methods for physical assets Engineering standards in asset management Education and training in asset management.
Keywords: Engineering; Industrial engineering; Production engineering; Engineering economics; Engineering economy; Quality control; Reliability; Industrial safety; Electrical engineering; Industrial organization; Engineering; Engineering Economics, Organization, Logistics, Marketing; Industrial and Production Engineering; Quality Control, Reliability, Safety and Risk; Signal, Image and Speech Processing; Communications Engineering, Networks; Industrial Organization; Electronic books